2013
DOI: 10.1016/j.ijnonlinmec.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear normal forced vibration modes in systems with internal resonance

Abstract: The new method of the forced resonance vibrations construction in mechanical systems with internal resonance is represented. According to this approach, the generalized theory of non-linear normal vibration modes by Shaw and Pierre, the modified Rauscher method and the harmonic balance method are combined with a new iterative computation procedure. The proposed approach is used in analysis of the single-disk rotor system with the isotropic-elastic shaft and the non-linear supports of Duffing type. Gyroscopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…48b) the explicit form of amplitudes defined in equations (26)(27) which lead to elimination of the second term in left side was considered. Also, with averaging of the rest secular terms of Eq.…”
Section: Solution Of First-order Approximation For Rigid Body With Tomentioning
confidence: 99%
See 2 more Smart Citations
“…48b) the explicit form of amplitudes defined in equations (26)(27) which lead to elimination of the second term in left side was considered. Also, with averaging of the rest secular terms of Eq.…”
Section: Solution Of First-order Approximation For Rigid Body With Tomentioning
confidence: 99%
“…The multiharmonic balance technique has been used in [25], to examine stability and vibrations analysis of a complex flexible rotor bearing system. Based on invariant manifolds approach, in [26] a new method has been developed for the determination of NNMs, incorporating Rausher and harmonic balance methods, and it has been applied to determine the dynamics of a spinning shaft with constant rotating speed with nonlinearities and inertia forces in the supports. It should be noted that in [22][23][24][25][26] the models were considering constant rotating speed and nonlinearities in bearings, without examination of non-constant rotating speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression is not changed if the phase of external load is varied by an arbitrary constant. This equivalent system of a new type can be also considered as the result of substitution (14) into (13) and division of the latter by Q2 . Due to the considerations above the system 20 The equivalent system (20) will be called the equivalent system o f 3rd type.…”
Section: Equivalent System Investigation Via Invariant Manifolds Methmentioning
confidence: 99%
“…In [2], the Duffing type equation was obtained by expanding the restoring and damping forces of a nonlinear isotropic Jeffcott rotor in Taylor series, and it was shown that there are ranges of rotational speed in which the periodic solution is unstable and some complicated solutions and even chaotic solutions exist. In [3], the nonlinear normal modes of the single disk rotor system with the isotropic elastic shaft and the nonlinear supports of Duffing type were analyzed considering gyroscopic effects, asymmetrical disposition of the disk on the shaft and internal resonance, in which, two different kinds of resonance regimes were summarized. In [4], a bladed rotor system considering the Duffing type nonlinearity for the stiffness of the blades and bearings was analyzed analytically, it reveals that two simple Hopf bifurcation points exist around the upper and lower critical speeds and both subcritical and supercritical Hopf bifurcations are expected due to the nonlinearity of the blade or bearing stiffness.…”
Section: Introductionmentioning
confidence: 99%